Differentially expressed immune-related genes in hemocytes of the pearl oyster Pinctada fucata against allograft identified by transcriptome analysis. Issue 62 (March 2017) - Wei, Jinfen; Liu, Baosuo; Fan, Sigang; Li, Haimei; Chen, Mingqiang; Zhang, Bo; Su, Jiaqi; Meng, Zihao; Yu, Dahui
Abstract: The pearl oyster Pinctada fucata is commonly cultured for marine pearls in China. To culture pearls, a mantle piece from a donor pearl oyster is grafted with a nucleus into a receptor. This transplanted mantle piece may be rejected by the immune system of the recipient oyster, thus reducing the success of transplantation. However, there have been limited studies about the oyster's immune defense against allograft. In this study, hemocyte transcriptome analysis was performed to detect the immune responses to allograft in P. fucata at 0 h and 48 h after a transplant. The sequencing reaction produced 92.5 million reads that were mapped against the reference genome sequences of P. fucata . The Gene Ontology (GO) annotation and the Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to identify all immune-related differentially expressed genes (DEGs). Compared with patterns at 0 h, a total of 798 DEGs were identified, including 410 up-regulated and 388 down-regulated genes at 48 h. The expression levels of interleukin receptor and toll-like receptor in hemocytes were increased significantly 48 h post-transplant, indicating that the oyster immune response was induced. Finally, altered levels of 18 randomly selected immune-related DEGs were confirmed by quantitative real-time PCR (qRT-PCR). Our results provide the basis for further analysis of the immune rejection of allotransplantation. Highlights: Immune molecules was identified in pearl oyster Pinctada fucata after transplantation. Compared with patterns at 0 h, a total of 798 DEGs were identified, at 48 h post transplantation. Acute Phase Proteins, like HSPs and Mts were expressed in the 0 h-48 h after transplantation. Toll-like receptor, Endocytosis and Apoptosis signal pathway play significant roles in the allograft immune mechanism.